Treatment of internal perforating root resorption using bioceramic dentin substitute and coronary reconstruction with Bulk Fill resins: Case Report - Yaringaño-Medina, Dora (2017)
Nonconventional duct treatment is reported in item 4.6 which shows internal perforating root resorption, which compromises the distal root, the use of a bioceramic dentin substitute cement called Biodentine as filling of said defect and its subsequent oral rehabilitation with Bulkfill condensable resin , patient is found with dental piece in function and asymptomatic.Key words: Root resorption, tomography. (Source: MeSH NLM)